Lifelong bound feet in China: a quantitative ultrasound and lifestyle questionnaire study in postmenopausal women - Qin, Ling (BMJ Open, 2015)
OBJECTIVE: The phenomenon of foot binding, also known as ‘lotus feet’, has an enduring and influential history in China. To achieve a man-made smaller foot size, lifelong foot binding may have had adverse effects on the skeleton. We investigated bone properties in postmenopausal women with bound feet, which may provide new information for developing countermeasures for prevention of fragility fractures. DESIGN: Population-based cohort study. PARTICIPANTS: This study involved 254 postmenopausal women aged 65–80, including 172 with bound feet and 82 age- and gender-matched control subjects, living in a remote region of China. OUTCOMES: Anthropometric, SF-36 Lifestyle Questionnaire and heel quantitative ultrasound (QUS) data were collected for the whole study population. A small subset of two cases was also invited for assessment of bone mineral density and microarchitecture at the distal tibia using high-resolution peripheral quantitative CT (HR-pQCT) and gait and balance tests. RESULTS: Women with bound feet had significantly lower QUS values than age-matched women with normal feet; this was supported by HR-pQCT data. However, SF-36 Questionnaire results did not reveal any statistically significant differences in any categorical responses, including physical functioning, general health vitality and physical component summary score, and number of previous fractures. No impairment of body balance was found in the small subset. CONCLUSIONS: The man-made changes caused by foot binding led to reduced physical activity, making the subjects prone to osteoporosis. Women with bound feet and osteoporosis did not have a higher incidence of fragility fractures than controls. This might be explained by compensation in physical activity to improve body balance, implying the importance of improving or maintaining body balance in overall prevention strategies against fragility fractures.